Peningkatan Pengetahuan Remaja Putri Tentang Keputihan Di Smpn 2 Banjarbaru - Zainab, Zainab,S.SiT.,M.Kes; Sajidah, Ainun; Ramie, Agustine (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2022)
Good knowledge is needed to be able to recognize, overcome, prevent vaginal discharge in young women, so that it can be treated according to the cause. The results of interviews with 10 students of SMPN 2 Banjarbaru, 5 of whom said that they did not know what vaginal discharge meant, 1 said that vaginal discharge was a liquid that comes out of the female genitalia, and 4 people did not know whether vaginal discharge was normal or not. happen. Of the 10 students, 4 of them said they had experienced vaginal discharge. The service method is carried out by increasing knowledge of young women (students at SMPN 2 Banjarbaru) using the lecture method and discussions related to vaginal discharge. After lectures and discussions, the female students were asked to explain vaginal discharge correctly. The evaluation that will be carried out is that the first is done before the lecture and the question and answer is carried out with a pre test (questionnaire) first to find out the extent of the knowledge of SMPN 2 Banjarbaru students about leucorrhoea, then after being given a lecture and discussion a post test (questionnaire) will be carried out. This training program very closely related to programs in improving adolescent reproductive health. This activity is very useful for providing the right information to young women about vaginal discharge so that after being given this information they can increase their knowledge about vaginal discharge and can take appropriate treatment if young women experience vaginal discharge and can prevent recurrent vaginal discharge